Risk Factors Associated With Reoperation and Disease-Specific Mortality in Patients With Medullary Thyroid Carcinoma - Kuo, Eric J. (JAMA Surg, 2017)
IMPORTANCE: The association of initial neck dissection with recurrence in medullary thyroid carcinoma (MTC) has not been evaluated on a population level to date. OBJECTIVE: To elucidate risk factors associated with reoperation in MTC and disease-specific mortality. DESIGN, SETTING, AND PARTICIPANTS: A retrospective analysis was performed of hospital data obtained from the California Cancer Registry and the Office of Statewide Health Planning and Development from January 1, 1999, through December 31, 2012. The dates of the analysis were January 1, 1999, to December 31, 2012. A population-based sample of 953 patients with MTC was identified. Patients who underwent thyroid surgery and had a minimum postoperative follow-up of 2 years (n = 609) were included in the analysis. EXPOSURE: Initial neck dissection in MTC. MAIN OUTCOMES AND MEASURES: Recurrent MTC leading to reoperation and disease-specific mortality. RESULTS: Of the 609 patients with MTC who underwent thyroid surgery, the mean (SD) patient age at diagnosis was 52.6 (17.5) years, and 60.8% (n = 370) of the patients were female. The mean (SD) tumor size was 2.8 (2.0) cm. Although initial central neck dissection is recommended by published MTC guidelines, only 35.5% (216 of 609) of patients underwent central neck dissection at the time of the initial thyroidectomy. The rate of reoperation was 16.3% (99 of 609), and the median time to reoperation was 6.4 months. The presence of lymph node metastasis increased the risk of reoperation (hazard ratio [HR], 3.43; 95% CI, 2.00-5.90), while central and lateral neck dissection performed at the initial operation was protective (HR, 0.53; 95% CI, 0.30-0.93). In patients who underwent reoperation, 45.5% (45 of 99) were disease free at a median follow-up of 7.7 years. Five-year disease-specific mortality for the entire cohort was 13.5% (82 of 609). Independent risk factors for disease-specific mortality included older age (HR, 1.36 per decade; 95% CI, 1.17-1.59), tumor size greater than 2 cm (HR, 2.83; 95% CI, 1.08-7.44 for >2 to 4 cm and HR, 2.89; 95% CI, 1.09-7.71 for >4 cm), and regional (HR, 4.77; 95% CI, 2.29-9.94) and metastatic (HR, 21.08; 95% CI, 9.90-44.89) disease. Reoperation was not associated with increased mortality. CONCLUSIONS AND RELEVANCE: Lymph node dissection may decrease recurrence leading to reoperation for patients with MTC. Reoperation is a viable strategy to achieve long-term disease-free survival in appropriately selected patients. Central neck dissection remains underused.